2020
DOI: 10.3389/fnagi.2020.590607
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Reserve, Leisure Activity, and Neuropsychological Profile in the Early Stage of Cognitive Decline

Abstract: In older adults with normal cognition, cognitive reserve (CR) is known to be associated with the neuropsychological profile. We investigated the association between comprehensive CR and detailed neuropsychological profile in the early stage of cognitive decline. Fifty-five participants with mild cognitive impairment or subjective cognitive decline completed the cognitive reserve index questionnaire (CRIq) that yielded total, education, working activity, and leisure time scores (CRI-Total, CRI-Education, CRI-Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 73 publications
4
18
0
1
Order By: Relevance
“…However, we found that a Life experience proxy of CR did potentially contribute to a compensation of cognitive performance in individuals with SCD. This is in line with recent studies reporting that the effect of CR is stronger for CR measures that quantify learning experiences occurring along with the lifespan (Bertoni et al, 2020; Lee et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…However, we found that a Life experience proxy of CR did potentially contribute to a compensation of cognitive performance in individuals with SCD. This is in line with recent studies reporting that the effect of CR is stronger for CR measures that quantify learning experiences occurring along with the lifespan (Bertoni et al, 2020; Lee et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, we found that a higher leisure time was correlated with lesser cognitive and functional HD decline over time in early manifest HD subjects. Our findings are in line with the documented evidence of the beneficial effect of leisure activities on cognitive decline in the early stages of non-HD neurodegenerative diseases [38]. Leisure activities, that is, the time when a person is not working and can relax and do things that they enjoy (i.e., reading, theater, television, driving, internet, gardening, music etc.)…”
Section: Discussionsupporting
confidence: 91%
“…Lifestyle activities in midlife significantly contributed to cognitive ability in late-life, independent of education and occupation. This has also been described in patients with either subjective memory decline or those who were diagnosed with a mild cognitive impairment (MCI) ( Lee et al, 2020 ). Whereas the educational background was not correlated with a comprehensive cognitive assessment, leisure activities were mostly predictive for executive function and visuospatial abilities.…”
Section: Introductionmentioning
confidence: 85%